Perancangan Sistem Informasi Pembuatan Surat Visum et Repertum Guna Menunjang Aspek Dokumen Medikolegal dengan Menggunakan Metode Agile - Mubarok, Muhammad Akmal; Yunengsih, Yuyun; Abdussalaam, Falaah (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2025)
The provision of Visum et Repertum services at Hospital X remains constrained because the process is carried out manually using Microsoft Word and Excel, resulting in duplicated tasks for staff. The objective of this study is to design an information system that supports the Visum et Repertum service process in hospitals in a structured, efficient, and well-documented manner. The system was developed using the Agile Development methodology, which includes planning, design, implementation, testing, documentation, and deployment. Microsoft Visual Studio 2012 was employed as the development platform, with Microsoft Access serving as the database. In this study, the author presents a more fully integrated visum information system encompassing features for data management, document generation, reporting, and archiving. The findings indicate that the developed information system is capable of supporting the visum service process within an integrated workflow, thereby enhancing staff productivity. Black-Box testing demonstrated that all features functioned according to user requirements without functional errors. Consequently, the system has been proven to reduce redundant workloads, minimize the risk of recording errors, and contribute to improving the efficiency and quality of visum services, while also supporting the sustainable integration of medical information.